Eine neue Art der Gattung Splendoroffula Clay & Meinertzhagen (1911) (Mallophaga). - Kéler, Stefan von (Contributions to Entomology = Beiträge zur Entomologie, 1961)
A new species of the genus Splendoroffula Clay & Meinertzhagen [Mallophaga), which is restricted to the family Musophagidae of African birds, is described. It is the seventh species of this genus, which contains probably still more species not yet discovered. Nomenclatural Acts sachtlebeni Kéler, 1961 (Splendoroffulla), spec. n.